1979
DOI: 10.1002/mrc.1270120213
|View full text |Cite
|
Sign up to set email alerts
|

The 13C NMR spectrum of coumarandione

Abstract: A re-ex8mh18tio11 of the -C NMR spectra of commrand~ 'one and isatin with the aid of proton-coupled -C NMR spectra and selective proton dewupling experiments is reported.The carbon chemical shifts of coumarandione (1) have recently been published.' Since the chemical shift data disagreed extensively with our data on related compounds, we repeated the preparation' of 1 and measured its 13C NMR spectrum, given in Table 1 together with the data of isatin (2). The assignment of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Different proposals for assignment of the signals have been published 42,[533][534][535] . This question was resolved by the obtention of the HETCOR spectrum, which revealed that the assignment proposed by Galasso, based on quantum mechanical calculations using the CNDO/S wave functions, was correct 534 .…”
Section: C Nmr Spectroscopymentioning
confidence: 99%
“…Different proposals for assignment of the signals have been published 42,[533][534][535] . This question was resolved by the obtention of the HETCOR spectrum, which revealed that the assignment proposed by Galasso, based on quantum mechanical calculations using the CNDO/S wave functions, was correct 534 .…”
Section: C Nmr Spectroscopymentioning
confidence: 99%
“…The acetate carbonyl (6 168.2) is assigned by its two-bond I 3 C -'~ coupling to the acetyl methyl hydrogens (6 2.43). The C-2 carbonyl is assigned on the basis of its chemical shift (8) and its lack of long range coupling.…”
mentioning
confidence: 99%
“…The ν C = O values are not modified by N-alkylation, N-acetylation leads to a hypsochromic shift of the lactum absorption of about 50-70 cm -1 while the ketone bands shift to 1750 cm -1 as cosenquence of the extension of a conjugation of the nitrogen lone pair with acetyl group [29]. posed by galasso based on quantum mechanical calculations using CNDO/S wave functions was correct [32]. This result allowed the correction of assignment of spectra of 1-acetyl isatin [33,34] and 1-Methylisatin and 3-dicyanomethyleneoxindole [35](▶table 3).…”
Section: Spectral Aspectsmentioning
confidence: 91%